2021
DOI: 10.1136/bmjopen-2020-048391
|View full text |Cite
|
Sign up to set email alerts
|

Multiorgan impairment in low-risk individuals with post-COVID-19 syndrome: a prospective, community-based study

Abstract: Objective To assess medium-term organ impairment in symptomatic individuals following recovery from acute SARS-CoV-2 infection. Design Baseline findings from a prospective, observational cohort study. Setting Community-based individuals from two UK centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
236
2
37

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(281 citation statements)
references
References 39 publications
6
236
2
37
Order By: Relevance
“…This age related perception of risk also explains why younger health care workers were less likely to be vaccinated, since the risk of severe disease has been reported to be low among younger age groups (37) although some studies have reported severe diseases among younger age groups. Andrea et al reported that almost 70% of the young 'low risk' with ongoing symptoms of COVID-19 had impairment in one or more organs four months after initial symptoms of SARS-CoV-2 infection (38). This study seems to suggest that even though low risk individuals have lower mortality rates, their severity of disease is seen by organ temporary impairment and follow up of this category is of public health importance.…”
Section: Discussionmentioning
confidence: 63%
“…This age related perception of risk also explains why younger health care workers were less likely to be vaccinated, since the risk of severe disease has been reported to be low among younger age groups (37) although some studies have reported severe diseases among younger age groups. Andrea et al reported that almost 70% of the young 'low risk' with ongoing symptoms of COVID-19 had impairment in one or more organs four months after initial symptoms of SARS-CoV-2 infection (38). This study seems to suggest that even though low risk individuals have lower mortality rates, their severity of disease is seen by organ temporary impairment and follow up of this category is of public health importance.…”
Section: Discussionmentioning
confidence: 63%
“…Neste estudo, a maioria das mulheres apresentou alterações no funcionamento intestinal, resultado semelhante ao encontrado em outros estudos (ANAYA et al, 2021;DENNIS et al, 2021). Ademais, foi identificada elevada prevalência de obstipação e diarreia, o que pode estar relacionado à infecção dos enterócitos pelo SARS-CoV-2, induzindo a inflamação nos tecidos que ocasiona distúrbios e redução da microbiota intestinal, os quais levam o aparecimento de sintomas que envolvem o trato gastrointestinal (TGI), sendo a diarreia o sintoma mais comumente relatado (ANDRADE et al, 2021;MAGHOOL et al, 2021).…”
Section: Discussionunclassified
“…In patients with persistent symptoms 5 months after initial SARS-CoV2 infection, 39% had echocardiographic findings of RV dilatation, 16% had findings of left ventricular (LV) diastolic dysfunction, and 10% had findings of LV systolic dysfunction [ 58 •]. Another prospective cohort study in low-risk patients with PCS 4 months post-infection found that 9% of patients had some systolic dysfunction on CMR with the incidence increasing as the severity of PCS increased [ 59 •]. Acute infection with SARS-CoV2 has also been linked to the development of Takotsubo cardiomyopathy [ 60 ].…”
Section: Heart Failure and Cardiomyopathiesmentioning
confidence: 99%
“…Myocarditis seems to develop in the post-acute setting of SARS-CoV2 infection regardless of patient condition and previous CVD risk factors. A prospective cohort study in otherwise low-risk patients in the general population with PCS 4 months post-infection found that 19% of patients had MRI evidence of myocarditis [ 59 •]. Risk of developing myocarditis remained even in highly trained athletes.…”
Section: Myocarditis and Pericarditismentioning
confidence: 99%